Pengaruh Senam Hamil Terhadap Penurunan Nyeri Punggung Bawah Pada Ibu Hamil TM III di Puskesmas Langsa Lama Kota - Sitorus, Rumondang; Husna, Asmaul; Simanullang, Ester; Sinaga, Asnita (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2022)
Utilization of the KIA handbook is still relatively low and constrained and most mothers also think that the KIA handbook is just an examination book so they do not understand the contents of the KIA handbook due to their lowknowledge and attitude of the mother. Purpose: This study aims to determine the effect of pregnancy exercise to reduce lower back pain in pregnant womenIII at the Langsa Health Center. Methods: The design of this study used anexperimental research type with a sample of 16 pregnant women with TM III at the Langsa Health Center. Results: The results of this study regarding therelationship between the use of the KIA handbook and the attitude of mothersin the implementation of immunization for pregnant women at the RawaBening Health Center, it can be concluded that the maximum number ofchildren with one child is (51.1%), the highest mother's education in elementaryschool (19.42%), and the mother's occupation is a housewife (30.66%), andUtilization of the KIA handbook shows good support at 62.2%. Mothers'attitude in carrying out immunization for pregnant women showed a positiveattitude of 75.6%